An Intelligent Road Traffic Signaling System Based On Vanet - Neha Garg; Dibyahash Bordoloi (Elementary Education Online, 2023)
The Road Traffic Data System is a crucial component of the highly developed transportation network of today. By feeding it real-time data from a variety of road sensors and vehicles, a wide area controller can improve traffic flow, trip time, and safety for road users. The VANET architecture provides a reliable foundation on which to construct a cutting-edge signal-control system. A unique VANET related road traffic signalling model is implemented, which has the potential to significantly improve traffic flow, fuel efficiency, and safety for drivers on the road. There is now a functioning VANET because of the utilisation of a decentralised architecture and distributed networking. We introduce a VANET-based Smart Road Traffic Signaling System in the initial section of this study (IRTSS). Preliminary results from a simulation model built on the OPNET framework are shown here. Simulations show that the proposed architecture can successfully manage traffic loads on an 802.11p enabled VANET network.